IMF Committee on Balance of Payments Statistics : Annual Report 2017. (Balance of Payments Statistics; Balance of Payments Statistics ;, 2018)
The 2017 Annual Report of the IMF Committee on Balance of Payments Statistics provides an overview of trends in global balance of payments statistics.